2005
DOI: 10.1111/j.1365-2125.2005.02436.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of indinavir alone and in combination with ritonavir in HIV‐1‐infected patients

Abstract: AimsThe aim of the study was to characterize the population pharmacokinetics of indinavir, define the relationship between the pharmacokinetics of indinavir and ritonavir, and to identify the factors influencing the pharmacokinetics of indinavir alone or when given with ritonavir.Methods HIV-1-infected patients being treated with an indinavir-containing reg imen were included. During regular visits, 102 blood samples were collected for the determination of plasma indinavir and ritonavir concentrations. Full ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…The PK model has already been described but no gene effect has been investigated using a population approach to date. The estimated parameters are in accordance with estimations obtained in other studies (Csajka et al, 2004;Goujard et al, 2005;Kappelhoff et al, 2005). The Wald test is the only test to detect an influence of ABCB1 exon 26 on the volume of distribution.…”
Section: Discussionsupporting
confidence: 82%
“…The PK model has already been described but no gene effect has been investigated using a population approach to date. The estimated parameters are in accordance with estimations obtained in other studies (Csajka et al, 2004;Goujard et al, 2005;Kappelhoff et al, 2005). The Wald test is the only test to detect an influence of ABCB1 exon 26 on the volume of distribution.…”
Section: Discussionsupporting
confidence: 82%
“…The final model estimates of CL/F and Vd/F were 21.3 L/hr/70 kg and 90.7 L/70kg, respectively, and these values are consistent with those reported in European patients 17, 18. Covariates reported to influence indinavir pharmacokinetics include concomitant ritonavir or non-nucleoside reverse transcriptase inhibitors (NNRTI) or ritonavir use, sex and body weight 11, 17.…”
Section: Discussionsupporting
confidence: 82%
“…Ritonavir is a HIV protease inhibitor, with strong CYP3A4-inhibiting properties and with only minor P-glycoprotein -inhibiting effects (14,15). Furthermore, the enhancement of the systemic exposure of CYP3A4 substrates by ritonavir is already a standard practice in the treatment of HIV patients with protease inhibitors (16,17). Recently, van Herwaarden et al (18) showed that the absence of Cyp3a activity in mice alone increased the systemic exposure of docetaxel after oral administration in vivo by 17.7-fold.…”
mentioning
confidence: 99%